2018
DOI: 10.12739/nwsa.2018.13.3.2b0114
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Organisation Commitment and Organisational Stress Behaviour in Disabled (Paralympic) Athletes

Abstract: The aim of this study is to investigate the organizational stress and organisational commitments levels of disabled (Paralympic) sports players, whether demographic properties affect organizational commitment and organizational stress, and the relationship between organizational commitment and organizational stress. In this study, surveys were given to Turkish sports players who participated in the 2016 Rio Paralympics Games, from which the study sample was constructed. Frequency, Mann Whitney U, Kruskal Walli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…A thorough literature review showed that there are limited studies on describing the reasons for starting sports for the individuals with hearing impairment. Studies mainly focus on sociologic, psychological, physiologic and physical gains of disabled individuals (Lewis & Fragala-Pinkham, 2005;Şirinkan, 2011;Taşkın, Karakoç, & Yüksek, 2015;Açak & Karademir, 2011;Işık, Kılıç, & Aksoy, 2017;Keskin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A thorough literature review showed that there are limited studies on describing the reasons for starting sports for the individuals with hearing impairment. Studies mainly focus on sociologic, psychological, physiologic and physical gains of disabled individuals (Lewis & Fragala-Pinkham, 2005;Şirinkan, 2011;Taşkın, Karakoç, & Yüksek, 2015;Açak & Karademir, 2011;Işık, Kılıç, & Aksoy, 2017;Keskin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%